Gender Role Concerning Trust of the Public Sector to Awareness of the Covid-19: A Multigroup Analysis - Andi Ernie Zaenab Musa (Otoritas : Jurnal Ilmu Pemerintahan, 2022)
This study was based on good governance theory, which considers the importance of citizens' trust in government in multiple contexts, including the public health crisis, such as the COVID-19 pandemic. Various studies have been conducted to determine the factors that influence people's behavior in times of contagion. This study looked at how citizens' risk perceptions of being infected and trust in government influenced their behavior. Additionally, gender role was assessed to see if it shaped behavioral changes. Data was collected from 505 respondents by a river sampling technique and analyzed using SmartPLS 3.0 software. The study found that the onset of coronavirus had a significant impact on citizens' risk perceptions of being infected, change of behaviors, and trust in government. Moreover, it was revealed that females were more conscious of the infection risks associated with the pandemic and, as such, behaved responsibly than their male counterparts. This study adds to the existing body of literature that government decisions in the best interests of citizens can help foster trust among citizens throughout a crisis.